30 Days to a More Powerful Business Vocabulary - Strutzel, Dan (Ascent Audio, 2021)
Business is just like any sector or topic, with its own language, customs, codes, and terminologies. Different aspects of business can have their own distinctive terminology, which can also overlap. In 30 Days to a More Powerful Business Vocabulary, Dan presents over 500 words and short expressions from a variety of different business categories. Each section introduces approximately twenty-five words. Each of the words are initially presented in a story or conversation, so you can experience the correct context in which the words are used. Dan then discusses each word or phrase and its definition. Finally, he reinforces the word and its meaning with another example in a sentence. And of course, Dan has you make all of the words a part of your permanent vocabulary by using his thirty-day learning program, based on well-known super-learning principles. There are four sections on banking and finance, four on marketing, and four on negotiation. Other sections focus on sales, entrepreneurship, human resources, e-business, leadership, and an all-new section on remote learning! As the world changes, language changes with it-and both are changing very fast. With 30 Days to a More Powerful Business Vocabulary, you'll keep pace with those changes and watch your career benefit as a result!
Online resource; Title from title page (viewed January 19, 2021)
Keywords: Audiobooks; Livres audio